Importance of Supply Integrity for In Vitro Fertilization and Embryo Culture - Morbeck, Dean E. (Seminars in Reproductive Medicine, 2012)
The quality of in vitro culture conditions is a key component of a successful clinical embryology laboratory. Many, but not all, supplies used in the embryology laboratory are screened by the supplier with a bioassay. Embryology laboratories use a variety of approaches to verify the quality of mineral oil, protein, and disposables before clinical use; however, a best practice has not been determined. Some laboratories test every supply, even those already screened by the supplier, whereas other laboratories perform as little testing as possible. Despite screening by the supplier, recent reports of embryo toxicity, specifically with mineral oil, highlight that the integrity of the supply system has gaps. This review describes current bioassay quality control testing and discusses how it applies to screening of products with documented lot-to-lot variation.
Keywords: quality control; mouse embryo assay; mineral oil